Strict Rules of Free Competition (about The Sveriges Riksbank Prize in Economic Sciences in Memory of Alfred Nobel 2020) - Y. P. Voronov (Мир новой экономики, 2021)
Studying the research results by Nobel prize-winning economists is a fundamentally important task for determining the most promising areas of development of Russian economic science. The author traces the connections between all these works and their predecessors’ work, many of whom were also awarded the Nobel prize in economics. Three lines of development of the predecessors’ achievements are identifid: information asymmetry, limited rationality, the design of market mechanism and new institutionalism. The article does not address the problems of auction theory related to its formal justifiation, which is part of mathematical economics and game theory. However, it is noted that this is an essential part of the laureates’ achievements. The article’s main conclusions are that the prize received for “improving the theory of auctions” fis into the broader economic research context. The winners solved the problems of maintaining free competition and reducing the market’s likelihood of monopolization. The author pays special attention to the results of the empirical analysis of actually implemented auctions. This analysis is divided into three parts, corresponding to the three stages of each auction: starting problems (distrust, the reputation of participants, etc.), the course of the auction (behaviour of participants and results, in particular, the “winner’s curse”.